Pengelolaan Pelayanan Akomodasi Villa Di Desa Adat Seminyak Pada Era New Normal - Kesumadewi, Putu Diah; Pratiwi, Anak Agung Manik (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2022.v10.i02.p11, 2022)
During the Covid-19 pandemic in early 2020, many villas in the Seminyak Traditional Village experienced a decrease in the number of guest visits. The new adaptation of service management in the new normal era in villa accommodation needs to be considered so that tourists are not afraid to carry out activities during their stay. This study aims to determine the management of villa accommodation services and to determine the tourists' perceptions of the quality of villa accommodation services in the Seminyak Traditional Village in the new normal era. The analysis in this study was carried out using a qualitative descriptive method and a Likert scale. Where this research adopts the concept of Management functions of POAC (Planning, Organizing, Actuating, Controlling) which are very well applied to realize good service in the new normal era. The management of villa accommodation services in the Seminyak Traditional Village in the new normal era in terms of service planning is carried out by preparing health protocols on the physical appearance of the villa and the physical appearance of the villa employees. The organization of the number of employees working is adjusted to the number of guest visits staying at the villa. The managerial directs staff to follow the procedure for starting work by using hand sanitizers and checking temperature. Direct supervision is carried out if the manager sees someone who does not comply with the health protocol, he will give a warning to the staff to continue to comply with the health protocol. Keywords: Management; Service; Villas; New Normal Era.